In situ synthesis of cobalt triphosphate on carbon paper for efficient electrocatalyst in dye-sensitized solar cell. (15th September 2020) - Gao, Xueman; Yue, Gentian; Cheng, Renzhi; Wu, Tianli; Fan, Leqing; Gao, Yueyue; Tan, Furui
Graphical abstract: Highlights: The carbon paper as the substrate was used to synthesize CEs in DSSC for the first time. The CoP3 /CP electrode exhibited low charge transfer resistance. The DSSC with CoP3 /CP electrode achieved the photoelectric conversion efficiency of 6.84%. Abstract: The cobalt triphosphide (CoP3 ) was grew on carbon paper (CP) by using a hydrothermal method and served as counter electrode (CE) catalyst in dye-sensitized solar cells (DSSCs). The morphology of the CoP3 /CP CE exhibits a regular fibrous structure, which provides a guarantee for its good electrochemical performance of the CE made from the cyclic voltammetry, Tafel test, etc. Various photoelectric performance tests also show that the DSSCs with CoP3 /CP CE achieves good photoelectric conversion efficiency of 6.84% under 100 mW·cm −2 illumination, which can compare to that of the DSSC assembled with the Pt (6.79%) CE. Metal phosphides are rarely used as CEs in DSSCs, and they will have a good promising alternative to the Pt electrode in the future.